2011
DOI: 10.2165/11208090-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate

Abstract: The AS04-adjuvanted human papillomavirus (HPV) 16/18 vaccine (Cervarix®) is a noninfectious recombinant vaccine produced using purified virus-like particles (VLPs) that induce a strong immunogenic response eliciting high levels of anti-L1 VLP antibodies that persist at levels markedly greater than those observed with natural infection. The vaccine adjuvant (AS04) is composed of monophosphoryl-lipid A, which enhances cellular and humoral immune response, adsorbed to aluminium hydroxide. The vaccine is indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(64 citation statements)
references
References 163 publications
1
63
0
Order By: Relevance
“…Given that loss-of-function MuRF1 mutations are found in human disease causing human hypertrophic cardiomyopathy [37], understanding the relationship between MuRF1 and hypertrophy is needed. Clinically, fenofibrate is used to treat dyslipidemia and is therapeutically valuable in lowering serum triglycerides in patients [20]. In the present study, we identified an unexpected link between fenofibrate and cardiac hypertrophy in MuRF1−/− hearts at doses that effectively lowered serum triglyceride levels after 8 weeks of treatment (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Given that loss-of-function MuRF1 mutations are found in human disease causing human hypertrophic cardiomyopathy [37], understanding the relationship between MuRF1 and hypertrophy is needed. Clinically, fenofibrate is used to treat dyslipidemia and is therapeutically valuable in lowering serum triglycerides in patients [20]. In the present study, we identified an unexpected link between fenofibrate and cardiac hypertrophy in MuRF1−/− hearts at doses that effectively lowered serum triglyceride levels after 8 weeks of treatment (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…The lipid-modifying effects of fenofibrate are mediated by its activation of PPARα in the liver [inhibiting the synthesis and release of very low density lipoproteins and increasing apolipoprotein A-I (apoA-I) and apolipoprotein A-II (apoA-II)] and small intestine (stimulating apoA-I), and an increase in lipoprotein lipase in skeletal muscle [19]. Fenofibrate also has more pleiotropic effects, not related to lipid metabolism including the reduction of fibrinogen, C-reactive protein, and other inflammatory markers that may contribute to its clinical efficacy, particularly microvascular disease [20]. MuRF1−/− mice were fed a standard mouse chow with 0.05% fenofibrate continuously for 8 weeks and followed by conscious echocardiography for function (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with statin monotherapy, fenofibrate monotherapy tends to improve triglyceride and HDL cholesterol levels to a greater extent, whereas statins improve LDL and total cholesterol levels to a larger degree. 175 In the Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) study, 9797 patients with diabetes mellitus who were not taking statins were randomized to micronized fenofibrate 200 mg daily or matching placebo for 5 years. Treatment with fenofibrate did not significantly reduce the risk of the primary outcome of cardiovascular death or nonfatal MI (HR, 0.89; 95% CI, 0.75-1.05; P=0.…”
Section: Triglyceride Managementmentioning
confidence: 99%
“…Moreover, potential benefits with fenofibrate therapy were suggested in terms of decreasing cardiovascular risk among patients with the most pronounced dyslipidemia, including those with the highest levels of triglycerides and lowest levels of HDL. 159,160,175,176 After CABG, elevated triglyceride levels may increase the risk of postoperative adverse outcomes. In an observational study of >25 000 patients who underwent primary isolated CABG between 1971 and 1998, investigators noted that a higher baseline triglyceride level at the time of surgery was significantly associated with a higher risk of repeat coronary revascularization (stent or reoperation) during long-term follow-up (P=0.002).…”
Section: Triglyceride Managementmentioning
confidence: 99%